Comparative study between 0.5% bupivacaine versus 0.5% ropivacaine in peribulbar anesthesia for cataract surgery - Neel Rana,; Shruti M. Shah,; Shrutika Parag Ved,; Srushti R Shah,; Patel Kushal Umeshkumar,; Panchal Pratik Vijaybhai, (Asian Journal of Medical Sciences, 2024)
Background: For intraocular surgery, the optimal local anesthetic agent must have a rapid onset of action and a sufficient duration of effect so as to enable a painless, motionless procedure without prolonging akinesia. Aims and Objective: This prospective, comparative observational study compares ropivacaine and 0.5% bupivacaine for cataract surgery peribulbar block. Hyaluronidase is utilized in both groups because it promotes local anesthetic diffusion. Material and Methods: Present prospective, observational, comparative study performed at the Department of Anesthesia Tertiary Care Teaching Institute of India for the duration of 1 year. All eligible patients were allocated in two groups as GROUP B and GROUP R. GROUP B: 10 mL of 0.5% bupivacaine and 15 I.U./mL of hyaluronidase. GROUP R: 10 mL of 0.5% ropivacaine and 15 I.U./mL of hyaluronidase. Patients were assessed for sensory block, eyelid, and ocular movements at an interval of 2 min, and Visual Analog Scale score for pain assessment. Results: Age and gender did not differ significantly between the two study groups, according to the findings. Comparable and similar patient characteristics distinguished the two study groups. (P>0.05). The difference in onset of eyelid motor blockade between the two groups was not statistically significant. The difference in the onset of motor blockade [ocular movement] between the two groups was not statistically significant (P>0.05). (P>0.05) Analgesia duration differed significantly between the two groups in a statistical sense. Ropivacaine exhibits a significantly prolonged duration of analgesic effect than bupivacaine (P≤0.05). Conclusion: Peribulbar block utilizing 0.5% ropivacaine is a more favorable and secure option for a local anesthetic that effectively extends postoperative pain alleviation, in comparison to the use of 0.5% bupivacaine.